Oral health-related knowledge, attitudes, and behaviors of students wearing fixed orthodontic appliances at Hue University of Medicine and Pharmacy - Nguyen, Ngoc Tam Dan; Nguyen, Gia Kieu Ngan; Nguyen, Le Minh Trang; Tran, Thien Man; Hoang, Anh Dao (Tạp chí Y Dược Huế, 2025)
Background: Oral hygiene is vital to each person’s oral health, especially in those undergoing orthodontic treatment. However, only some people know how to properly and effectively clean their teeth. Therefore, assessing oral hygiene knowledge, attitudes, and behaviors is necessary. Objectives: To determine the level of knowledge, attitudes, and behaviors of oral hygiene of students wearing fixed orthodontic appliances and to examine the relationship between knowledge, attitude, behavior of oral hygiene, and plaque status in students who are wearing fixed orthodontic appliances. Subjects and methods: A cross-sectional study was carried out on 80 The Hue University of Medicine and Pharmacy students wearing fixed orthodontic appliances. The study was conducted from 06/2023 to 09/2023. Results: 82.35% of students have adequate oral hygiene knowledge, 68.63% have a positive attitude, and 63.73% have proper behavior. The average plaque index on teeth is 0.988 ± 0.412, and our study found only a moderate positive association between plaque status and oral hygiene knowledge (r=0.307, p=0.005). Conclusion: Knowledge, attitude, and oral hygiene behavior are important factors that directly affect the effectiveness of the orthodontic process. Therefore, it is necessary to promote the provision of adequate oral hygiene knowledge, positive attitudes, and proper behaviors to improve the oral health of healthcare students - who have an impact on their health community in the future.